The Legacy of Early Abuse and Neglect for Social and Academic Competence From Childhood to Adulthood. Issue 5 (15th January 2018) - Raby, K. Lee; Roisman, Glenn I.; Labella, Madelyn H.; Martin, Jodi; Fraley, R. Chris; Simpson, Jeffry A.
Abstract : This study used data from the Minnesota Longitudinal Study of Risk and Adaptation ( N  =   267) to investigate whether abuse and neglect experiences during the first 5 years of life have fading or enduring consequences for social and academic competence over the next 3 decades of life. Experiencing early abuse and neglect was consistently associated with more interpersonal problems and lower academic achievement from childhood through adulthood (32–34 years). The predictive significance of early abuse and neglect was not attributable to the stability of developmental competence over time, nor to abuse and neglect occurring later in childhood. Early abuse and neglect had enduring associations with social (but not academic) competence after controlling for potential demographic confounds and early sensitive caregiving.